Comparison of ROM, perceived tightness, and kinetic variables during balance, walking, and running tasks in athletes with and without hamstring tightness using sensor insoles - Fereydounnia, S.; Shadmehr, A.; Salemi, P.; Amiri, S. (Sport Sciences for Health, 2022)
Objective The length of the hamstring muscles plays an important role in human movements. The aim of the present study was to compare ROM, perceived tightness, and kinetic variables during balance, walking, and running tasks in athletes with and without hamstring tightness.